2011
DOI: 10.1007/s13595-011-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic use of very high-frequency radar and discrete-return lidar for estimating biomass in temperate hardwood and mixed forests

Abstract: Abstract• Introduction Accurate estimation of aboveground biomass is essential to better understand the carbon cycle in forest ecosystems.• Methods The objective of this study was to determine whether biomass in temperate hardwood forests is better estimated using very high-frequency radar data (from BioSAR) alone or in combination with small-footprint discrete-return lidar data (both profiling and scanning). The study area was in the Appomattox-Buckingham State Forest, Virginia, USA (78°41′W, 37°25′N). Aboveg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The M2sp.autopls model showed a good estimation of AGB, with a lower RMSE (11.17) than the mean RSE (39.4) of all the DRL studies, and a RSE% of 8.9% lower than 20% (or ±20 t·ha −1 , the greater of the two), which is considered the accuracy requirement of a global forest biomass mapping mission for at least 80% of grid cells [22]. Compared to other studies [22], the M2sp.autopls model showed better results than those found for the following: coniferous forest (R 2 = 0.64, RMSE = 28.5 t·ha −1 [74] and R 2 = 0.75, RMSE = 45.6 t·ha −1 [75]); deciduous forest (R 2 = 0.71, RMSE = 39.3 t·ha −1 ) [75]; taiga forest (R 2 = 0.72, RMSE = 14.2 t·ha −1 ) [76]; and tropical forest (R 2 = 0.36, RMSE = 22.8 t·ha −1 [77]; R 2 = 0.78 [78]; and R 2 = 0.72, RMSE = 40.2 t·ha −1 [33]). Other studies reported higher accuracies, such as in rainforest (R 2 = 0.90, RMSE = 38.3 t·ha −1 ) [79] and temperate forest (R 2 = 0.89, RMSE = 50.2 t·ha −1 [80] and R 2 = 0.93, RMSE = 33.9 t·ha −1 [81]), among other results reported in the literature.…”
Section: Discussionmentioning
confidence: 84%
“…The M2sp.autopls model showed a good estimation of AGB, with a lower RMSE (11.17) than the mean RSE (39.4) of all the DRL studies, and a RSE% of 8.9% lower than 20% (or ±20 t·ha −1 , the greater of the two), which is considered the accuracy requirement of a global forest biomass mapping mission for at least 80% of grid cells [22]. Compared to other studies [22], the M2sp.autopls model showed better results than those found for the following: coniferous forest (R 2 = 0.64, RMSE = 28.5 t·ha −1 [74] and R 2 = 0.75, RMSE = 45.6 t·ha −1 [75]); deciduous forest (R 2 = 0.71, RMSE = 39.3 t·ha −1 ) [75]; taiga forest (R 2 = 0.72, RMSE = 14.2 t·ha −1 ) [76]; and tropical forest (R 2 = 0.36, RMSE = 22.8 t·ha −1 [77]; R 2 = 0.78 [78]; and R 2 = 0.72, RMSE = 40.2 t·ha −1 [33]). Other studies reported higher accuracies, such as in rainforest (R 2 = 0.90, RMSE = 38.3 t·ha −1 ) [79] and temperate forest (R 2 = 0.89, RMSE = 50.2 t·ha −1 [80] and R 2 = 0.93, RMSE = 33.9 t·ha −1 [81]), among other results reported in the literature.…”
Section: Discussionmentioning
confidence: 84%
“…Nichol and Sarker (2011) recently presented a study where texture feature ratios extracted from AVNIR-2 and HRG data were successfully employed in modelling biomass with R 2 up to 0.939. LiDAR, SAR, and even Landsat data have been also employed in biomass estimation studies (Kronseder et al 2012;Banskota et al 2011;Vastaranta et al 2014;Langner et al 2012;Sandberg et al 2011). Stem volume and basal area have been estimated through a synergy of ALS with airborne colour infrared (CIR) and AVNIR-2 data (Hou et al 2011).…”
Section: Forestry Monitoringmentioning
confidence: 99%
“…As forests are one of the major carbon sinks in the global ecosystem, the aboveground biomass (AGB) is a primary variable related to the amount of carbon flowing in the cycle. Therefore, more accurate AGB estimations are needed to understand the carbon cycle in forest ecosystems [1][2][3]. Spatially explicit measurement of global biomass also supports the Reduction of Emissions due to Deforestation and Forest Degradation (REDD) mechanism and the international effort to reduce anthropogenic greenhouse gas emissions [4][5][6][7].…”
Section: Introductionmentioning
confidence: 92%